Correction: Transgenic PDGF-BB/sericin hydrogel supports for cell proliferation and osteogenic differentiation. (19th May 2021) - Wang, Feng; Hou, Kai; Chen, Wenjing; Wang, Yuancheng; Wang, Riyuan; Tian, Chi; Xu, Sheng; Ji, Yanting; Yang, Qianqian; Zhao, Ping; Yu, Ling; Lu, Zhisong; et al.
Abstract : Correction for 'Transgenic PDGF-BB/sericin hydrogel supports for cell proliferation and osteogenic differentiation' by Feng Wang et al., Biomater. Sci., 2020, 8, 657–672, DOI: ; 10.1039/C9BM01478K .